Studi Kemampuan Layanan Wudhu Masjid / Mosque Ablution Service Capability Study - Mafra, Ramadisu; Zulfikri, Zulfikri; Riduan, Riduan (Universitas muhammadiyah palembang, 2022)
It is natural for men whos pray in congregation at mosque, trying to get the primacy of praying in congregation without missing imam's takbiratul ihram, because many good things will be obtained, including freedom from the torments of hell and from hypocrisy. However various restrictive factors, cause many congregations to be left behind in takbiratul ihram, and even become masbuk. One of them is because the queue for ablution caused by number of ablution faucets is not proportional with capacity of congregations that must be served, especially during Friday prayers. This study is important to do in order to know the factual ability of ablution services at mosques in the city of Palembang, as well as comparison with SNI 8135:2015 standards, so that it is expected to be a reference for planning mosque ablution facilities. Data collected using a field survey method at 35 mosques in the Palembang city. Analysis of service estimates using the calculus method, then presented in tables and diagrams as well as narrative descriptions. Results prove that the duration of ablution of 64.2 seconds is significantly valid with a margin of error of 6.39%. Total of 85.71% mosques have an average ablution service capability of 48.24% of the total capacity of the mosque at 15-minute intervals, with an average ratio of 1 faucet : 31 male congregation, or only 43.33% of the number of faucets based on SNI 8153:2015 standard.